Effect of the ergostim and amino acids on vegetative growth characteristics and mineral content of hot pepper (Capsicum annuum L.) - Rakhaa Shakir Mohammed AL-nassrallah; Ahmed Dinar Khalaf AL-Asadi (University of Thi-Qar Journal of agricultural research, 2023)
The experiment was carried out in one of the unheated greenhouses at the research station of the College of Agriculture and Marshes / University of Thi Qar, Al-Mustafawiya during the season 2021-2022. To study the effect of spraying with Ergostim and amino acids on the vegetative growth characteristics and the mineral content of the hot pepper under protected cultivation, and the cultivation of the hybrid cultivar Barbarian, the experiment was carried out using a randomized complete block design and the experiment included two factor and three replications consisting of four concentrations of Ergostim (0 and 1, 2, and 3) ml L-1 and three concentrations of amino acids (0, 2, and 4) ml L-1 by using complete randomized block design with three replicates. The averages of the treatments were compared according to the Least Significant Differences (LSD) test at the probability level of 0.05. The results showed that spraying of the Ergostim nutrient solution on the leaves had a significant effect on increasing each of (plant height, leaf area, number of branches, and the percentage of nitrogen, phosphorus and potassium in the leaves) at a concentration of (3 ml L-1), as rates were recorded 100.90 cm plant-1 ,133.01 dm2 plant-1, 11.24 branch plant-1, 12.99%, 2.32%, 1.08%, respectively. As for the amino acids, the concentration (4 ml L-1) achieved the highest levels in the above-mentioned traits. It reached 100.74 cm Plant-1 ,108.63 cm 2 Plant-1 ,10.26 cm branch plant -1, 12.93%, 2.28%, 1.03%, respectively.